2018
DOI: 10.1088/1361-648x/aad575
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in a misfit layered compound (SnSe)1.16(NbSe2)

Abstract: The large size single crystals of (SnSe)(NbSe) misfit layered compound were grown and superconductivity with T of 3.4 K was first discovered in this system. Powder x-ray diffraction and high resolution transmission electron microscopy clearly display the misfit feature between SnSe and NbSe subsystems. The Sommerfeld coefficient γ inferred from specific-heat measurements is 16.73 mJ mol K, slightly larger than the usual misfit compounds. The normalized specific heat jump [Formula: see text] is about 0.98, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…We calculated the lattice parameters of (SnSe) 1.16 (NbSe 2 ) 2 from the SAED patterns and summarized in table 1. The values of a and b are close to those of (SnSe) 1.16 (NbSe 2 ) for both subsystems [14], but the space group of two subsystems are both changed. We can obtained the incommensurate factor as 1+y=2a 2 /a 1 ≈1.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…We calculated the lattice parameters of (SnSe) 1.16 (NbSe 2 ) 2 from the SAED patterns and summarized in table 1. The values of a and b are close to those of (SnSe) 1.16 (NbSe 2 ) for both subsystems [14], but the space group of two subsystems are both changed. We can obtained the incommensurate factor as 1+y=2a 2 /a 1 ≈1.…”
Section: Resultsmentioning
confidence: 58%
“…Moreover, it is found that about 4% Se are substituted by Br, which is unavoidably caused by the bromine transport agent. Such a halogen contamination also occurs in other MLCs such as (SnSe) 1.16 (NbSe 2 ) and (PbSe) 1.12 (TaSe 2 ) which were grown by the same CVT method [14,15]. Figure 1(b) shows the XRD pattern of a (SnSe) 1.16 (NbSe 2 ) 2 single crystal at room temperature, and the inset is a photograph of the typical as-grown single crystal.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations